A pet-friendly workplace policy to enhance the outcomes of an Employee Assistance Programme (EAP) - Lombard, A. (Antoinette) (University of Pretoria, 2013)
Dissertation (MSoc.Sc (Employee Assistance Programme))--University of Pretoria, 2006.